Astrocyte - Physiology and Pathology 2018
DOI: 10.5772/intechopen.72975
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptors in Astroglia: Chronology, Controversies, and Contradictions from a Complex Molecule

Abstract: The neurocentric theory dismissed for decades the role of glia in information handling within the central nervous system (CNS). Nevertheless, almost 3 decades ago, this started to change and today astrocytes are considered relevant players for this function. Astrocytes "listen" to neuronal communication, regulate it, and respond at the cellular and synctitial level. Ionotropic glutamate NMDA receptor (NMDAR) is critical in CNS. It mediates synaptic neuronal communication and it is involved in different mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 156 publications
(200 reference statements)
0
8
0
Order By: Relevance
“…12,28 More importantly, proton concentration has been found critical for NMDAR flux inhibition [15][16][17] and, 1mM NMDA has been previously found to regulate astrocyte and neuronal functions. 5,18,19 As shown in Figure 1A (left column), the maximal averaged response was observed with NMDA/pH6 (∫(ΔF/F 0 ) = 5.49) (The averaged response is that obtained averaging ΔF/F 0 responses from all experiments and cells tested in the same condition). In contrast, NMDA/pH7 only slowly and slightly increased iCa 2+ (∫(ΔF/F 0 ) = 2.81), whereas NMDA/pH5 also increased iCa 2+ (∫(ΔF/F 0 ) = 3.37), but to a lesser extent than NMDA/ pH6.…”
Section: Flux-independent Ica 2+ Response Is Elicited Mainly By Ph6mentioning
confidence: 73%
See 4 more Smart Citations
“…12,28 More importantly, proton concentration has been found critical for NMDAR flux inhibition [15][16][17] and, 1mM NMDA has been previously found to regulate astrocyte and neuronal functions. 5,18,19 As shown in Figure 1A (left column), the maximal averaged response was observed with NMDA/pH6 (∫(ΔF/F 0 ) = 5.49) (The averaged response is that obtained averaging ΔF/F 0 responses from all experiments and cells tested in the same condition). In contrast, NMDA/pH7 only slowly and slightly increased iCa 2+ (∫(ΔF/F 0 ) = 2.81), whereas NMDA/pH5 also increased iCa 2+ (∫(ΔF/F 0 ) = 3.37), but to a lesser extent than NMDA/ pH6.…”
Section: Flux-independent Ica 2+ Response Is Elicited Mainly By Ph6mentioning
confidence: 73%
“…[15][16][17] Moreover, the NMDA concentration used here has been found by us and others to regulate astrocyte and specific neuronal functions. 5,18,19 In our previous work, we also demonstrated that intracellular Ca 2+ (iCa 2+ ) rise was sensitive to competitive NMDAR inhibitors or GluN1 subunit Knock Down, demonstrating NMDAR involvement. Surprisingly, iCa 2+ rise was insensitive to NMDAR pore blocker MK-801 or extracellular Ca 2+ depletion, but it was blocked by InsP 3 R and RyR inhibitors.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations